2015
DOI: 10.1097/md.0000000000001142
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Quantitative Calculations of Primary Tumor Metabolic Activity Using F-18 FDG PET/CT as a Predictor of Survival in 92 Patients With High-Grade Bone or Soft Tissue Sarcoma

Abstract: To assess the prognostic value of primary tumor metabolic activity in patients with high-grade bone sarcomas (BS) or soft tissue sarcomas (STS) using F-18 FDG PET/CT.A single-site, retrospective study including 92 patients with high-grade BS or STS. Pretreatment F-18 FDG PET/CT scan was performed. Clinical data were registered. Accuracy of maximum standardized uptake value of primary tumor (SUVmax) and tumor-to-background (T/B) uptake ratio as prognostic variables and identification of cut-off values to group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…We have previously reported the shortcomings of the prognostic use of SUV max and tumor-to-background uptake ratio in the same study cohort, especially in subgroup analysis of patients with high-grade BS. 27 The volume-based F-18 FDG PET imaging markers MTV and TLG attempt to overcome the limitations of SUV max , by including several important prognostic tumor characteristics, such as heterogeneity, size, and burden; that is, an inclusion of the total volume and total activity of metabolically active tumor cells. This theoretical advantage has been verified by several studies reporting significant prognostic properties in terms of prediction of treatment response and survival in a diversity of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported the shortcomings of the prognostic use of SUV max and tumor-to-background uptake ratio in the same study cohort, especially in subgroup analysis of patients with high-grade BS. 27 The volume-based F-18 FDG PET imaging markers MTV and TLG attempt to overcome the limitations of SUV max , by including several important prognostic tumor characteristics, such as heterogeneity, size, and burden; that is, an inclusion of the total volume and total activity of metabolically active tumor cells. This theoretical advantage has been verified by several studies reporting significant prognostic properties in terms of prediction of treatment response and survival in a diversity of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A single-site, retrospective study from July 1st 2002 to December 31st 2012 including 92 consecutive patients, with clinical characteristics and study design as previously reported 27 (47 men; 45 women; median age 49.8 [11.2–86.3] years; Table 1 ). The patients were referred for further evaluation and/or surgical treatment and were included in the study according to the following criteria: first, histologically verified high-grade BS (N = 37) or STS (N = 55) according to either the French Federation of Cancer Centers Sarcoma Group (FNCLCC) grading system (STS) 28 or the grading recommendations of the College of American Pathologists (BS), 29 second, no previous history of malignancy, third, underwent an on-site pre-operative 18 F-FDG PET/CT scan for staging, and fourth, a minimum follow-up period of 1 year for survived patients.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies supported that baseline SUV max using 18 FDG-PET/CT demonstrates independent properties beyond histologic grading for prediction of survival. Andersen et al [11] reported a cut-off point of 9, whereas Hwang et al [7] and Skamene et al [12] revealed cut-off points of 5.8 and 10.3, respectively. In our study, findings were consistent with the literature stating that higher SUV max has significantly poor survival outcomes in sarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenic features, maximum standardised uptake value on FDG-PET, apparent diffusion coefficient on MRI are all linked to tumour grade and metastatic risk, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] but no evidence for their use in distinguishing OM from PM…”
Section: Functional Imaging Featuresmentioning
confidence: 99%